Risk Factors and Outcome of Obstructed Labour: A Study in Rajshahi Medical College Hospital, Rajshahi, Bangladesh - Shahreen, Homaira; Khatun, Rokeya (TAJ: Journal of Teachers Association, 2022)
Introduction: Obstructed labour is one of the major causes of maternal mortality (8%) in Bangladesh. It is also responsible for high rate of maternal and fetal morbidity, if we can identify causes of obstructed labour, determine the outcome & complications in our country it may be helpful to find out the way to prevent this disease. Objective: The purpose of the present study was to determine the risk factors as well as to assess the outcome of obstructed labour. Methods: This study is a prospective observational study has been done in Department of Obstetrics and Gynaecology in Rajshahi Medical College Hospital, Rajshahi, Bangladesh during July 2016 to December 2018. Hundred patients who were admitted with obstructed labour during study period were included in this study. A detailed history included socio-demographic feature, obstetric history, features of obstruction, intrapartum events were recorded to detect risk factors. Condition of patients, mode of delivery, preoperative and postoperative complications, maternal and fetal outcomes were recorded. Results: This study was one hundred (100) cases with features of obstructed labour were selected. The highest frequency was found among the unbooked, primigravid patients that were illiterate or only having primary education level. 84% in primi-gravidae and 10% in multi gravidae had come from medium socio-economic group and only 2% in case of primigravidae came from good economic classes. Revealed that 56% in primigravidae and 68% in multi gravidae of study population did not cross primary education level. the causative factors of obstructed labour, 46% in primigravidae and 42% multi gravidae cases were due to cephalopelvic disproportion with varying degrees of contracted pelvis, 52% in primigravidae and 58% multi gravidae cases caused by malpositions and malpresentations, 2% in primigravidae was due to cervical fibroid. The medical causes of obstructed labour in the study population were cephalopelvic disproportion 42-46%. One patient died due to post-partum hemorrhage among 10(10.0%) cases. Conclusion: In this study the incidence of obstructed labour was very high. The commonest cause was cephalopelvic disproportion followed by fetal malpostion and malpresentation. TAJ 2021; 34: No-2: 80-89